ADKAR : a model for change in business, government, and our community - Hiatt, Jeff. (Loveland, Colorado : Prosci Learning Center Publications, 2006)
In his first complete text on the ADKAR model, Jeff Hiatt explains the origin of the model and explores what drives each building block of ADKAR. Learn how to build awareness, create desire, develop knowledge, foster ability and reinforce changes in your organization. The ADKAR Model is changing how we think about managing the people side of change, and provides a powerful foundation to help you succeed at change.
Includes bibliographical references (p. 145-146).
Keywords: Organizational change; Organizational change -- Management; Leadership